2003
DOI: 10.1029/2002gl016848
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling large scale variations in methane emissions from wetlands

Abstract: [1] Global wetlands are, at estimate ranging 115 -237 Tg CH 4 /yr, the largest single atmospheric source of the greenhouse gas methane (CH 4 ). We present a dataset on CH 4 flux rates totaling 12 measurement years at sites from Greenland, Iceland, Scandinavia and Siberia. We find that temperature and microbial substrate availability (expressed as the organic acid concentration in peat water) combined explain almost 100% of the variations in mean annual CH 4 emissions. The temperature sensitivity of the CH 4 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
288
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(322 citation statements)
references
References 33 publications
(42 reference statements)
28
288
1
5
Order By: Relevance
“…This is probably due to the important role of precipitation for the wetland emissions in southern Europe, while for temperate and boreal regions the seasonal variation of wetland emissions is mainly driven by temperature (e.g. Christensen et al, 2003;Hodson et al, 2011). In contrast to the discussed four models, NAME derives much smaller seasonal variations, and for western Europe, eastern Europe, and EU-28 with the opposite phase (small maximum in winter).…”
Section: European Ch 4 Emissionsmentioning
confidence: 75%
“…This is probably due to the important role of precipitation for the wetland emissions in southern Europe, while for temperate and boreal regions the seasonal variation of wetland emissions is mainly driven by temperature (e.g. Christensen et al, 2003;Hodson et al, 2011). In contrast to the discussed four models, NAME derives much smaller seasonal variations, and for western Europe, eastern Europe, and EU-28 with the opposite phase (small maximum in winter).…”
Section: European Ch 4 Emissionsmentioning
confidence: 75%
“…Root exudates lead to an increase in substrate availability in the form of easily decomposable organic compounds, which can be used by methanogens to produce CH 4 (Aulakh et al, 2001;Christensen et al, 2003). There are studies that found positive correlations between radiation or net ecosystem production and CH 4 flux (Whiting and Chanton, 1993;Joabsson and Christensen, 2001), although there are also studies that found the opposite (Mikkelä et al, 1995;Ström et al, 2005).…”
Section: Effect Of Other Environmental Factors On Chmentioning
confidence: 96%
“…Globally, wetlands are the largest natural source of CH 4 emissions to the atmosphere (IPCC, 2013). Because wetland CH 4 emissions are highly sensitive to soil temperature and moisture conditions (Saarnio et al, 1997;Friborg et al, 2003;Christensen et al, 2003;Moore et al, 2011;Glagolev et al, 2011;Sabrekov et al, 2014), there is concern that they will provide positive feedback to future climate warming (Gedney et al, 2004;Eliseev et al, 2008;Ringeval et al, 2011). This risk is particularly important in the world's high latitudes because they contain nearly half of the world's wetlands (Lehner and Döll, 2004) and because the high latitudes have been and are forecast to continue experiencing more rapid warming than elsewhere (Serreze et al, 2000;IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%